Ultrasound findings of diffuse metastasis of gastric signet-ring-cell carcinoma to the thyroid gland - Morita, Koji (J Med Ultrason (2001), 2016)
It has been shown that metastases to the thyroid from extrathyroidal malignancies occur as solitary or multiple nodules, or may involve the whole thyroid gland diffusely. However, diffuse metastasis of gastric cancer to the thyroid is extremely rare. Here, we report a case of a 74-year-old woman with diffuse infiltration of gastric adenocarcinoma (signet-ring-cell carcinoma/poorly differentiated adenocarcinoma) cells in the thyroid. The pathological diagnosis was made based on upper gastrointestinal endoscopy with biopsy and fine-needle aspiration cytology of the thyroid. An 18F-FDG PET/CT revealed multiple lesions with increased uptake, including the bilateral thyroid gland. On thyroid ultrasound examination, diffuse enlargement with internal heterogeneity and hypoechoic reticular lines was observed. On color Doppler imaging, a blood-flow signal was not detected in these hypoechoic lines. These findings were similar to those of diffuse metastases caused by other primary cancers, such as lung cancer, as reported earlier. Therefore, the presence of hypoechoic reticular lines without blood-flow signals is probably common to diffuse thyroid metastasis from any origin and an important diagnostic finding. This is the first report to show detailed ultrasound findings of diffuse gastric cancer metastasis to the thyroid gland using color Doppler.